Analysis of the Influence of Product Innovation on Consumer Purchasing Decisions - Sirmauly Valentina Purba (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the influence of product innovation on consumer purchasing decisions. In the face of increasingly fierce business competition, product innovation has become an important strategy used by companies to attract consumer interest and increase competitiveness. This study uses a quantitative approach with an associative method. Data were collected by distributing questionnaires to 100 respondents who are consumers of the products studied, using a purposive sampling technique. The research instrument used a Likert scale and has undergone validity and reliability tests. The data analysis technique used was simple linear regression with the help of statistical software. The results show that product innovation has a positive and significant effect on consumer purchasing decisions, with a regression coefficient value of 0.678 and a significance value of 0.000 (<0.05). In addition, the coefficient of determination (R²) value of 0.536 indicates that product innovation is able to explain 53.6% of the variation in purchasing decisions, while the rest is influenced by other factors outside the study. These findings indicate that the higher the level of product innovation carried out by a company, the higher the likelihood of consumers making a purchase. Therefore, companies are advised to continue to innovate according to consumer needs and preferences in order to improve purchasing decisions and maintain competitive advantage.